THE EFFECTIVENESS OF THE PROTISTA COURSE TEACHING MODULE IS BASED ON THE RESULTS OF THE PERONOSPORA MANSHRICA LABORATORY TEST ON SOYBEAN SEED ( GLYCINE MAX) - Marsila Marsila; Aloysius Hardoko; Sukartiningsih Sukartiningsih (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
The purpose of this research is the development of a module for the protist course in the Biology Education Study Program (S1) FKIP Mulawarman University which is carried out by following the instructional design stages with the ADDIE approach, which consists of 5 stages: Analyze, Design, Develop, Implement, and Evaluate. The data on the feasibility of the module teaching materials were obtained from the validation results by the Protista material experts and teaching materials experts. Meanwhile, the practicality test of the module was carried out by the respondent students of the Biology Education Study Program, FKIP, Mulawarman University. To see the effectiveness of the teaching module, pretest and posttest were carried out. The results showed that the percentage of the feasibility of the module material by material expert validators was 85.65 % with very valid criteria (decent) with slight improvements. The percentage of module eligibility by learning module development experts (teaching materials) is 86, 70% with very valid criteria (adequate). The results of the practicality of the material aspects of Class A and Class B are 84.6% very practical and the learning aspect is 83.2% very practical. Based on the results of the normalized gain test analysis, it shows that the average value of the N-Gain index for class A is 79.08% including the Effective category, while the average N-Gain index for class B is 78.07% including the Effective category. Meanwhile for the category of obtaining the average N-gain Score for class A is 0.79 including the high category and for the category, the average acquisition of the N-gain Score for class B is 0.82 which is also included in the high category. The results of this study indicate that the module teaching materials are very feasible and very practical to be used by students or lecturers in protist lecture activities on the material "Fungus: characteristics; classification: class Phycomycetes(Oomycetes)